Renal Cell Carcinoma Presenting with Cutaneous Metastasis: A Case Report. (20th July 2010) - Onak Kandemir, Nilufer; Barut, Figen; Yılmaz, Kıvanç; Tokgoz, Husnu; Hosnuter, Mubin; Ozdamar, Sukru Oguz
Abstract : Renal cell carcinoma is the most common kidney tumor in adults. Cutaneous metastasis is a rare first symptom of the disease. This paper describes the diagnosis of a renal cell carcinoma that was indicated by cutaneous metastasis in the head and neck region, and considers the etiopathogenesis of such cases. A careful skin examination is important to detect cutaneous metastasis associated with renal cell carcinomas. Metastatic skin lesions in the head and neck region must be taken into consideration during a differential diagnosis.